The Work of Sales Representatives in the Context of Interactions and Work with Emotions - Pawłowska, Beata (Qualitative Sociology Review, 2020)
The article aims to present the interactional encounters undertaken within their professional context by the studied group of Polish sales representatives concerning their emotions and emotional work. It is an internally diverse group made of individuals skillful in managing their emotions, as well as the ones of others. Additionally, the professional group at hand is purposefully trained to acquire skills in the area of managing emotions. The concepts of Everett Hughes (1958) concerning work, Arlie Hochschild (1983) in the context of emotional labor, Anselm Strauss (1993) pointing to the coexistence of emotions and action, and Robert Prus (1997) on the contextual nature of social life are the theoretical underpinning of the article. They all derive from the interpretative paradigm and fit into the theoretical premises of symbolic interactionism, assuming the constant construction of social reality as a result of interactions undertaken by social actors (see: Blumer 2007). It is the nature of their interactions with customers, colleagues, and direct and indirect superiors that determines the specificity of a sales representative’s work situation. The analyses presented in the article are based on qualitative research using unstructured interviews, conversational interviews, and observations.